Designing Observer Based Variable Structure Controller for Large Scale Nonlinear Systems - Reza Ghasemi (IAES International Journal of Artificial Intelligence (IJ-AI), 2013)
Designing observer based decentralized fuzzy adaptive controller is discussed for a class of large scale non-canonical nonlinear systems with unknown functions of the subsystems in this paper. The On-line adaptation of the controller and the observer parameters, boundedness of the output and the observer errors, robustness against external disturbance are the advantages of the proposed method. The simulation results show the promising performance of the proposed method.DOI: http://dx.doi.org/10.11591/ij-ai.v2i3.2025